Beneficiation Of Brazilian Diatomite For Filtration Application Industry - S. C. A. Franca; M. T. Millqvist; A. B. Luz (Society for Mining, Metallurgy & Exploration, 2002)
Laboratory experiments were performed on a Brazilian diatomite from Bahia State to produce an industrial product for use as a filter aid. Bench and pilot plant tests were conducted consisting of: diatomite desegregation, organic matter and clay removal, filtration, drying and calcination. Calcination temperature and sodium carbonate addition influenced diatomite particle size distribution. Optimum filtration rates for calcined products were obtained at 900°C and 47 min. residence time with 3% (w/w) of sodium carbonate addition, and resultant products met specifications imposed on filter aids.